Incompetent managers — modern realities in Russian companies - E. V. Medvedev (Омский научный вестник: Серия "Общество. История. Современность")
In the article, the author raises the question of the incompetence of modern managers. The purpose of the study is to analyze such a category as managers, as well as to identify the reasons for their incompetence and offer recommendations for improving the situation. In conclusion, the author draws a conclusion about the work done and proposes a set of measures to increase the level of competence of our managers. The results of the study can be used in the practical activities of the country’s enterprises, as well as in the authorities.